Synaptic protein CSF levels relate to memory scores in individuals without dementia - Wesenhagen, Kirsten E. J.; de Leeuw, Diederick M.; Tomassen, Jori; Gobom, Johan; Bos, Isabelle; Vos, Stephanie J. B.; Martinez-Lage, Pablo; Tainta, Mikel; Popp, Julius; Peyratout, Gwendoline; Tsolaki, Magda; Vandenberghe, Rik; et al. (Alzheimer's research & therapy, 2025)
We investigated how cerebrospinal fluid levels of synaptic proteins associate with memory function in normal cognition (CN) and mild cognitive impairment (MCI), and investigated the effect of amyloid positivity on these associations. We included 242 CN (105(43%) abnormal amyloid), and 278 MCI individuals (183(66%) abnormal amyloid) from the European Medical Information Framework for Alzheimer's Disease Multimodal Biomarker Discovery (EMIF-AD MBD) and the Alzheimer's Disease Neuroimaging Initiative (ADNI). For 181 (EMIF-AD MBD) and 36 (ADNI) proteins with a synaptic annotation in SynGO, associations with word learning recall were analysed with linear models. Subsets of synaptic proteins showed lower levels with worse recall in preclinical AD (EMIF-AD MBD: 7, ADNI: 5 proteins, none overlapping), prodromal AD (EMIF-AD MBD only, 27 proteins) and non-AD MCI (EMIF-AD MBD: 1, ADNI: 7 proteins). The majority of these associations were specific to these clinical groups. Synaptic disturbance-related memory impairment occurred very early in AD, indicating it may be relevant to develop therapies targeting the synapse early in the disease.